ANALISIS FAKTOR-FAKTOR PENENTU PERSISTENSI LABA (Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Namira Fitri Nadya; Djusnimar Zultilisna (Yayasan Akrab Pekanbaru, 2018)
Earning that has quality, is earning that able to predict future earnings. Earning persistence, is one way to assess the quality of earning by predicting future earnings, it is especially useful for investors in allocating the right funds to invest. This study aims to investigate factors that determining earnings persistence such as cash flow volatility, sales volatility, leverage and firm size, either simultaneously or partially on property and real estate companies listed on the Indonesia Stock Exchange period 2012-2016. The sampling technique used is purposive sampling and obtained 160 research samples from 32 companies. Data analysis method in this research is panel data regression analysis by using software Eviews version 9. The result of this research shows that cash flow volatility and sales volatility has positive significant effect to earning persistence, leverage has significant negative effect to earning persistence while firm size has no significant effect to earning persistence. Keyword: Cash flow volatility, sales volatility, leverage, firm size,